Effects of introduced exotic tree species on Collembola communities: The importance of management techniques - SOUSA, J. P.; Vingada, J. V.; Barrocas, H.; DAGAMA, M. M. (PEDOBIOLOGIA, 1997)
Studies of the impact of the substitution of autochthonous forests by plantations of exotic tree species (a quite common phenomenon in Southern European countries) on soil arthropod communities (mainly Collembola and Acarina) generally deal with the effects of the exotic species per se and disregard the management techniques used. In this study the impact of the introduced Eucalyptus globulus on the Collembola communities of Quercus ilex ballota and Quercus suber stands was analysed. Since the autochthonous tree species are similar (in terms of leaf type and the ability to produce litter) the main objective was to examine the effects of the different management techniques used in the two plantations of Eucalyptus. (i) There is a significant difference in management techniques used in the Eucalyptus plantations leading to differences in habitat configuration: the plantation associated with the Helm-Oak stand is used for cellulose paste production, with periodic removal of the shrub and herbaceous layers; the other plantation, close to the Cork-Oak stand, is not managed at all, presenting an abundant shrub layer. (ii) in both cases, the substitution of the Oak species by Eucalyptus caused a disruption of the Collembola communities, although it was more pronounced in e. ilex ballota vs E. globulus (station 1) than in e. suber vs E. globulus (station 2). The number of individuals, the number of taxa and diversity parameters are in most cases greater under Oak species but more evident in station 1. (iii) Given these results, the influence of the factor `'management technique-habitat configuration'' in analysing and interpreting effects of exotics on soil arthropod communities is discussed.
IX International Colloquium on Apterygota, DUBLIN, IRELAND, 1996IX International Colloquium on Apterygota, DUBLIN, IRELAND, 1996The following values have no corresponding Zotero field: pub-location: VILLENGANG 2, D-07745 JENA, GERMANY publisher: GUSTAV FISCHER VERLAG
Keywords: Collembola community disruption; EUCALYPTUS; Quercus illex; Quercus suber

Effects of introduced exotic tree species on Collembola communities: The importance of management techniques - Sousa, J P; Vingada, J V; Barrocas, H; DaGama, M M (PEDOBIOLOGIA, 1997)
Studies of the impact of the substitution of autochthonous forests by plantations of exotic tree species (a quite common phenomenon in Southern European countries) on soil arthropod communities (mainly Collembola and Acarina) generally deal with the effects of the exotic species per se and disregard the management techniques used. In this study the impact of the introduced Eucalyptus globulus on the Collembola communities of Quercus ilex ballota and Quercus suber stands was analysed. Since the autochthonous tree species are similar (in terms of leaf type and the ability to produce litter) the main objective was to examine the effects of the different management techniques used in the two plantations of Eucalyptus. (i) There is a significant difference in management techniques used in the Eucalyptus plantations leading to differences in habitat configuration: the plantation associated with the Helm-Oak stand is used for cellulose paste production, with periodic removal of the shrub and herbaceous layers; the other plantation, close to the Cork-Oak stand, is not managed at all, presenting an abundant shrub layer. (ii) in both cases, the substitution of the Oak species by Eucalyptus caused a disruption of the Collembola communities, although it was more pronounced in e. ilex ballota vs E. globulus (station 1) than in e. suber vs E. globulus (station 2). The number of individuals, the number of taxa and diversity parameters are in most cases greater under Oak species but more evident in station 1. (iii) Given these results, the influence of the factor `'management technique-habitat configuration'' in analysing and interpreting effects of exotics on soil arthropod communities is discussed.
IX International Colloquium on Apterygota, DUBLIN, IRELAND, 1996
Keywords: Collembola community disruption; EUCALYPTUS; Quercus illex; Quercus suber

Influence of leaf litter type on the chemical evolution of a soil parent material (sandstone) - Madeira, M; Ribeiro, C (Biogeochemistry, 1995)
The influence of leaves of Quercus suber L. and Eucalyptus globulus Labill. and needles of Pinuspinaster Ait. on a sandstone substrate was assessed through lysimetric studies during a ten-year period at a site in Central Portugal. The decomposition rate of Q. suber leaf litter was similar to that of E. globulus and higher than that of P pinaster needle litter. The proportion of nitrogen released from the Q. suber leaf litter was higher than that lost from the other organic species. Such a release was proportional to the initial nitrogen content in the substrates. The concentrations of both NHa-N and NO3-N were much higher in leachates collected under Q. suber leaf litter than in those collected under the other organic substrates. A similar trend was found in the leachates collected under the mineral substrate influenced by the studied organic substrates. The leachate concentrations of mineral N (especially NOs-N) were higher from the mineral substrate under Q. suber leaf litter than from this organic substrate itself. The mineral substrate under leaf litter of E. globulus or needle litter of P pinaster showed an increase in exchangeable base cations and pH values, and a decrease in extractable Al. Conversely, in the substrate with Q. suber leaf litter there was only a slight increase in exchangeable base cations and pH values, and a decrease in extractable Al. These results combined with those obtained in soils underE. globulus plantations indicate that changes found in these soils are due to soil and forest m
Keywords: decomposition rate; elemental fluxes; EUCALYPTUS; Leaching; leaf litter; Pinus pinaster; Quercus suber; soil chemistry

RUPTURE IN A COLLEMBOLA COMMUNITY STRUCTURE FROM A QUERCUS-ROTUNDIFOLIA LAM FOREST DUE TO THE REAFFORESTATION WITH EUCALYPTUS-GLOBULUS LABILL - Sousa, J P; DaGama, M M (EUROPEAN JOURNAL OF SOIL BIOLOGY, 1994)
Here we compare Collembola populations from a Quercus rotundifolia forest and an Eucalyptus globulus plantation. The overall analysis of data (using both diversity and similarity measures) have shown clear signs of rupture on the structure of collembola populations, with the fauna associated with the Quercus stand being richer (in exclusive and preferential species) and more abundant than the one connected with the Eucalyptus. Data also reflects the faunal stratification between organic and mineral horizons, with the majority of species being associated with upper soil layers in detriment of mineral horizon. These disruptions may be related to profound alterations of habitat characteristics, particularly the frequent removal of shrub vegetation and leaf layer, result of the forestry practices connected with the preparations and management of the eucalyptus plantation.
Keywords: Collembola; EUCALYPTUS; holm-oak; REAFFORESTATION

RUPTURE IN A COLLEMBOLA COMMUNITY STRUCTURE FROM A QUERCUS-ROTUNDIFOLIA LAM FOREST DUE TO THE REAFFORESTATION WITH EUCALYPTUS-GLOBULUS LABILL - SOUSA, J. P.; DAGAMA, M. M. (EUROPEAN JOURNAL OF SOIL BIOLOGY, 1994)
Here we compare Collembola populations from a Quercus rotundifolia forest and an Eucalyptus globulus plantation. The overall analysis of data (using both diversity and similarity measures) have shown clear signs of rupture on the structure of collembola populations, with the fauna associated with the Quercus stand being richer (in exclusive and preferential species) and more abundant than the one connected with the Eucalyptus. Data also reflects the faunal stratification between organic and mineral horizons, with the majority of species being associated with upper soil layers in detriment of mineral horizon. These disruptions may be related to profound alterations of habitat characteristics, particularly the frequent removal of shrub vegetation and leaf layer, result of the forestry practices connected with the preparations and management of the eucalyptus plantation.
The following values have no corresponding Zotero field: pub-location: DEPT UNIV PROFESSIONNEL REVUES SCIENTIFIQUES TECHNIQUE 11 RUE GOSSIN, F-92543 MONTROUGE, FRANCE publisher: GAUTHIER-VILLARS
Keywords: Collembola; EUCALYPTUS; holm-oak; REAFFORESTATION

EFFECTS OF REAFFORESTATION BY EUCALYPTUS-GLOBULUS ON THE EDAPHIC COLLEMBOLA - DaGama, M M; NOGUEIRA, A; DOSSANTOS, AFAM (REVUE D ECOLOGIE ET DE BIOLOGIE DU SOL, 1991)
The authors studied the effects of reafforestation by Eucalyptus globulus on the edaphic Collembola, by means of factorial analysis of correspondences applied to the study of Collembola populations, occurring in coppices of Quercus suber and in Eucalyptus globulus plantations.
Keywords: Collembola; EUCALYPTUS; FACTORIAL; REAFFORESTATION

Thermal decomposition of wood in oxidizing atmosphere. A kinetic study from non-isothermal TG experiments - Cordero, T; Rodriguez-Maroto, J M (Thermochimica acta, 1991)
The kinetics of thermal decomposition of four wood species in oxygen-bearing atmo- spheres of 5, 10 and 20% molar Oz concentrations have been studied from temperature-pro- grammed experiments carried out at 5, 10 and 20 K mm ’ -* heating rate. Devolatihzation as weII as combustion of the reaminin g solid have been considered to analyze the weight loss curves. The homogeneous volume reaction (VR) model has been used to describe devolatihza- tion, whereas for solid combustion the grain model has been also checked. A two-stage approach has been used to fit the conversion-time curves and to derive the corresponding apparent kinetic parameters. The VR/VR (pyrolysis/combustion) combination provided a better description of the experimental (~-1 curves than the VR/grain combination. Hohn oak and cork oak showed very close reactivities, whereas some differences were observed for aleppo pine and eucalyptus.
Keywords: Aleppo pine; combustion (voyant); Cork oak; EUCALYPTUS; Holm oak; Kinetic model; pyrolysis; Wood